Design, Implementation, and Evaluation of The Training Course Based on the Flipped Classroom in Relation to the Interpretation of the Report of the Measurement of Physical Harmful Factors in the Work Environment for Undergraduate Students of Occupational Health - Rohollah Fallah Madvari; fatemeh Keshmiri (Babol University of Medical Sciences, 2023)
Background and purpose: The use of the flipped classroom method as an interactive method in the blended learning process is expanding in medical sciences universities. The present study aimed to assess the effect of education using the flipped classroom on students' perception, learning, and satisfaction in interpreting the report of measuring physical harmful factors in the workplace. Materials and methods: The present study is a quasi-experimental design (pre-test-post-test). The research population consisted of 25 professional health students of Shahid Sadougi University of Medical Sciences, who studied in this school during 2021-2022. All the students were included in the study by the census. The educational intervention was conducted using the flipped classroom method in order to develop student's skills in interpreting the report of measuring physical harmful factors in the workplace. Measuring students' views, learning, and satisfaction was conducted by the survey. Data were analyzed using descriptive tests and analysis. Findings: The results showed that the average (standard deviation) of students' learning knowledge scores before the intervention was 51.66(9.06)  (average level). After the intervention 73.54(12.53)  (good level), which was reported significantly has improved (P=0.0001). Students' satisfaction was reported with an average of 4.00 (0.73), which is at a favorable level. Their preparation has a positive and significant relationship with practicality and importance. Also, practicality has a positive and significant relationship with importance, perspective, and satisfaction, and students' understanding has a positive and significant relationship with satisfaction. Conclusion: Using the flipped classroom method for interpreting and analyzing the results of tests and measurements had a positive effect on students' learning and satisfaction. Also, students' understanding scores regarding the preparation and applicability of education were evaluated at the desired level. It is recommended to use active and cooperative methods such as the flipped classroom method, which emphasizes the application of students' learning.